2012
DOI: 10.1186/1471-2431-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Population based trends in mortality, morbidity and treatment for very preterm- and very low birth weight infants over 12 years

Abstract: BackgroundOver the last two decades, improvements in medical care have been associated with a significant increase and better outcome of very preterm (VP, < 32 completed gestational weeks) and very low birth weight (VLBW, < 1500 g) infants. Only a few publications analyse changes of their short-term outcome in a geographically defined area over more than 10 years. We therefore aimed to investigate the net change of VP- and VLBW infants leaving the hospital without major complications.MethodsOur population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
88
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 26 publications
9
88
2
5
Order By: Relevance
“…Over the last two decades, survival after very preterm birth (VP; gestational age at birth <32 weeks) and very low birth weight (VLBW; <1500 grams) has improved considerably [1].…”
Section: Neonatal Treatment Philosophy In Dutch and German Nicus: Heamentioning
confidence: 99%
“…Over the last two decades, survival after very preterm birth (VP; gestational age at birth <32 weeks) and very low birth weight (VLBW; <1500 grams) has improved considerably [1].…”
Section: Neonatal Treatment Philosophy In Dutch and German Nicus: Heamentioning
confidence: 99%
“…A study by Luu and colleagues [28] revealed that VPT/VLBW children who showed a catch-up in cognitive performance had low rates of neonatal complications and neurosensory impairment, highly educated mothers and were members of the ethnic majority. Overall, about 70 % of all VPT/VLBW children born in Switzerland do not exhibit severe neonatal complications and neurosensory impairment, which increases the possibility of normal cognitive functions later in development [36].…”
Section: Introductionmentioning
confidence: 99%
“…The aims of the study were to investigate whether (a) VPT/VLBW children of both age groups performed poorer than controls (deficit hypothesis) or caught up with increasing age (delay hypothesis) and (b) whether VPT/VLBW children displayed a similar pattern of performance increase in EF with advancing age compared with the controls. As low rates of neonatal complications and neurodevelopmental impairment (IQ≥ 85) have been shown to be a crucial factor facilitating a catch-up in preterm-born children [28], only VPT/VLBW children with no or minimal neonatal cerebral brain lesions and no or minimal neurodevelopmental impairment were included, which represent the major subgroup of the VPT/VLBW population [36].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a considerable increase in the survival rate of very-lowbirth-weight (VLBW, <1 500 g) neonates over the last few decades as a result of improvements in medical care (Ruegger, Hegglin, Adams & Bucher, 2012). This increase is particularly recorded in developed countries where improved outcome following medical intervention in the neonatal intensive care unit (NICU) has been well documented (Darlow, Cust & Donoghue, 2003).…”
mentioning
confidence: 99%